Transforming Social Capital to Strengthen Local Government Resilience in Hazard-Prone Areas - A. Junaedi Karso; Rudi Hardi; Abdul Samad Baryalai (Journal of Contemporary Governance and Public Policy, 2025)
This study examines the transformation of social capital in strengthening local government resilience to natural disaster risks in Gowa, Indonesia—an area highly vulnerable to multiple natural hazards. Employing a quantitative research design, the study utilises Structural Equation Modelling (SEM) via Partial Least Squares (PLS-SEM) to conduct regression analysis. Data were collected through a structured survey involving 150 respondents from 15 institutions, including government agencies, private sector actors, non-governmental organisations (NGOs), and disaster response volunteers. The survey comprised 72 statement items across eight variables, ensuring the dataset’s validity and reliability. The findings indicate that strengthening social bonds, fostering community collaboration, and enhancing trust in local institutions significantly contribute to reducing the impacts of disasters by enabling swift responses and improving recovery efforts. These results underscore the vital—yet often underappreciated—role of social capital in disaster risk management and resilience building. The study calls for policy interventions that promote community cohesion and institutional trust, demonstrating that social dimensions are central to effective and sustainable disaster risk reduction. Moreover, the research aligns with the United Nations Sustainable Development Goals (SDGs), particularly Goal 11 (Sustainable Cities and Communities) and Goal 13 (Climate Action), by advocating for socially inclusive, community-driven resilience strategies.